Perlambatan Waktu Perjalanan Akibat Perlintasan Sebidang Kereta Api (Studi Kasus : Jalan Hos Cokroaminoto, Kebon Jahe Tanjung Karang) - Prasetyo, Tri Makmur; Putra, Sasana; Ofrial, Siti Anugrah Mulya Putri (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
A level crossing is a form of an intersection where a railway line crosses a highway at the same level. This may result a long queue which is caused by changes in velocity and density of vehicles. Hence, research should be conducted in order to determine changes in vehicle velocity which occurs when the gated crossing is opened on that road section. One of the level crossings between the railway line and the highway can be found on Jalan Hos Cokroaminoto, Kebon Jahe, Tanjung Karang. This study aims to determine changes in traffic velocity that occur on Jalan Hos Cokroaminoto based on the equivalent of light vehicle (EKR) value obtained from the headway ratio method. The results of the observation show that the average velocity of vehicle when crossing the railway line is 3.12 km/hour, while when entering the crossing is 19.48 km/hour so that there is a decrease in velocity in the amount of 16.36 km/hour.Keywords: Shock Wave, Light Vehicle Equivalence (EKR), Rasio Headway Method, Greenberg Method